PERLINDUNGAN HUKUM KONSUMEN DALAM HAL PELAKU USAHA PENGEMBANG RUMAH SUSUN YANG SUDAH DINYATAKAN PALIT (STUDI TERHADAP KEMANGGISAN RESIDENCE) - Illona .; Anna Maria Tri Anggraini (Jurnal Hukum Adigama, 2018)
The needs for apartment are currently increasing as the population increases and as availability of land becomes limited. The demand for such apartment is utilized by the developers to build and market the apartment in the community. However, with the high desire of developers in meeting the demands for apartment, it does not always coincide with the needs of the consumers for a decent place to live and have a guarantee of legal security. Therefore, the author proposes issue about how is the law protection of consumer in terms of apartment developers as business actors who have declared bankruptcy viewed from the perspective of Consumer Protection Law? The research method that the researcher uses for the issue is academy purposes methods with library data collection techniques. After conducted the research of preventive consumer legal protection, the law has been regulated in Regulation Number 8 Year 1999. But with Consumer Protection Act yet has not provided maximum protection to consumer. The violation of the consumer rights have given uncertainty to the consumers who will buy the apartment units. Plenty of developers whose business activities in the apartment field perform their activities with no good faith. While the repressive consumer legal protection has been regulated. The settlement can be done both inside and outside the court. However, the settlement has not been so regulated that it leaves a gap for business actors to avoid from responsibility to compensate consumers.